The Authority of the Batam City Regional Government and the Batam City Free Trade and Free Port Authority in the Business Licensing Process Through the Online Single Submission Risk Based Approach Based on Legal Certainty - fetarina, Lisdwi; Widayati, Widayati (UNISSULA Semarang, 2025)
The Unitary State of the Republic of Indonesia is a state based on law. This concept is stated in Article 1 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia which reads: The State of Indonesia is a state of law. The consequence of this article is that every action, whether it is the action of a citizen or the action of a state administrator (government), must be based on law and must not conflict with the applicable positive law (ius constitutum). The approach method used in this study is empirical juridical. According to Abdul Kadir Muhamad, empirical juridical research is: